Special Economic Zones in the Global South: Between integrated spaces and enclaves – a literature review - Kiesel, Carolina; Dannenberg, Peter (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
Special Economic Zones (SEZs) have gained massively in popularity worldwide and particularly in the Global South. However, they are also discussed as a controversial economic policy instrument. Some analyses view SEZs as promising spaces with integrative linkages, while other studies see them as enclaves marked by spatial and economic segregation. To shed light on the various and partly contradictory perceptions of SEZs, this paper reviews literature on SEZs in the Global South and suggests a differentiated and more comprehensive view for SEZ analyses in order to understand their different characteristics, interactions, and the related processes between SEZs and their host regions. Our review goes beyond dichotomies of viewing SEZs as enclavistic or integrated spaces. Instead, it systematically outlines how even a single SEZ can integrate into regions in some ways, while remaining disintegrated in other ways. Here, we build on recent studies of SEZs in the Global South, employing the enclave approach as a conceptual basis, and include conceptual works on economic linkages and global production networks.